Characteristics of bacterial contamination of the mammary gland secretion of lactating cows with subclinical mastitis - A. M. Pasternak; V. I. Koshevoy; S. V. Naumenko; M. L. Radzykhovskyi; P. M. Skliarov (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Subclinical mastitis (SCM) in lactating cows is a common disease characterized by a change in the composition of mammary gland secretion, especially due to an increase in number of somatic cells in it over a long period of time. Etiologically, this disease arises as a result of the pathogenic effect of mixed infections caused mainly by bacteria of Staphylococcus and Streptococcus genera. It should be noted that due to high prevalence, reduction of milk yield and changes in the physical and chemical properties of milk of cows, SCM is a more important problem than clinical forms of mastitis. Thus, the aim of the work was to determine the main causative agents of SCM in lactating cows and their resistance to antibiotics in order to justify the feasibility of using alternative means in the schemes of therapy and prevention of this disease. During the bacteriological examination of mammary gland secretion, streptococci were differentiated by morphological and cultural-biochemical properties, and the pathogenicity of staphylococci was determined by the ability to coagulate rabbit blood plasma in the conditions of the testing laboratory of Smartbiolab LLC (Kharkov) in 2019–2021. Subclinical mastitis in lactating cows was determined using a sample with 5 % dimastine and a thermographic study. Before taking milk samples, the udders were wiped with 70 % alcohol, and the milk was expressed in sterile tubes. The samples were transported in plastic boxes with cooling elements (at a temperature of 8–10 °С) and were examined no later than 4 hours after the moment of selection. The results of research in selected samples Streptococcus spp., which has β-hemolytic properties, was found in 42.9 % of samples, E. coli with hemolytic properties in 28.6 %, and Staphylococcus haemolyticus and Staphylococcus aureus in 14.2 % each. The detected pathogens were characterized by the following indicators of antibiotic resistance: E. coli isolates were insensitive to 8 antibiotics (ampicillin, penicillin, streptomycin, neomycin, spectinomycin, spiramycin, lincomycin, chloramphenicol), and Streptococcus spp. (penicillin, amoxicillin, amoxicillin + clavulonic acid, streptomycin, norfloxacin, gatifloxacin, lincomycin) and Staphylococcus aureus (ampicillin, penicillin, amoxicillin, streptomycin, oxytetracycline, ceftiofur and lincomycin) up to 7, respectively.